Underwater Image Enhancement by Adaptive Gray World and Differential Gray-Levels Histogram Equalization - Wong, Siaw Lang; Paramesran, Raveendran; Taguchi, Akira (Ştefan cel Mare University of Suceava, 2018)
Most underwater images tend to be dominated by a single color cast. This paper presents a solution to remove the color cast and improve the contrast in underwater images. However, after the removal of the color cast using Gray World (GW) method, the resultant image is not visually pleasing. Hence, we propose an integrated approach using Adaptive GW (AGW) and Differential Gray-Levels Histogram Equalization (DHE) that operate in parallel. The AGW is applied to remove the color cast while DHE is used to improve the contrast of the underwater image. The outputs of both chromaticity components of AGW and intensity components of DHE are combined to form the enhanced image. The results of the proposed method are compared with three existing methods using qualitative and quantitative measures. The proposed method increased the visibility of underwater images and in most cases produces better quantitative scores when compared to the three existing methods.